2020
DOI: 10.1111/pcn.13099
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol use in Australia during the early days of the COVID‐19 pandemic: Initial results from the COLLATE project

Abstract: The effects of social isolation measures used to control the spread of COVID-19 are negatively impacting the mental health of many. One of the consequences of exposure to disasters/pandemics is an increase in alcohol use. The current study aimed to examine what predisposing (distal) and pandemic-related (proximal) factors were associated with increased drinking in the wake of the COVID-19 pandemic. Methods: On 1 April 2020, 5158 Australians completed a survey from the COvid-19 and you: mentaL heaLth in AusTral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

22
186
12
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(223 citation statements)
references
References 23 publications
22
186
12
3
Order By: Relevance
“…Among a sample of 4,276 university students in the US surveyed at the end of March 2020, those with more symptoms of depression and anxiety reported a greater increase in alcohol consumption compared to those with fewer symptoms (24). Although increases in alcohol consumption were associated with higher levels of anxiety, depression, and stress symptoms among a sample of 1,491 anonymously surveyed Australian adults in April 2020 (25), a different study among 4,462 Australian adults conducted around the same time found that only depression and stress, but not anxiety, were indicators of a reported increase in alcohol use (26). To date, no studies have examined changes in alcohol use during COVID-19 in a genetically informed sample of adults.…”
Section: Introductionmentioning
confidence: 87%
“…Among a sample of 4,276 university students in the US surveyed at the end of March 2020, those with more symptoms of depression and anxiety reported a greater increase in alcohol consumption compared to those with fewer symptoms (24). Although increases in alcohol consumption were associated with higher levels of anxiety, depression, and stress symptoms among a sample of 1,491 anonymously surveyed Australian adults in April 2020 (25), a different study among 4,462 Australian adults conducted around the same time found that only depression and stress, but not anxiety, were indicators of a reported increase in alcohol use (26). To date, no studies have examined changes in alcohol use during COVID-19 in a genetically informed sample of adults.…”
Section: Introductionmentioning
confidence: 87%
“…Likewise, addictive behavior is one of the mental health issues raised by researchers with respect to the COVID-19 pandemic [12][13][14], including an increased risk of alcohol problems, drug problems and behavioral addictions including problem gambling [15]. For example, researchers have expressed the concerns that alcohol consumption may be increased by the pandemic [16] and early data demonstrate that a significant minority of the population may have increased their consumption in line with other changes in everyday lives [17]. While substance use disorders are typically likely to be less prevalent in adult elite athletes during their active career [9], concerns have been raised about a likely increased risk in problem gambling.…”
Section: Introductionmentioning
confidence: 99%
“…B efore the onset of COVID-19, the USA was experiencing rising rates of alcohol use, high-risk drinking, and alcohol use disorder (AUD) with negative consequences including increases in alcohol-related morbidity and mortality. 1 As a result of the COVID-19 pandemic, it is likely that the USA will see further increases in alcohol consumption similar to those observed in the UK 2 and Australia, 3 raising significant public health concerns. In the USA, while effective screening, medication, and behavioral treatments are available, only 7.9% of adults with AUD received any alcohol treatment in 2018.…”
mentioning
confidence: 99%
“…Excessive alcohol use is a common response to coping with stress 3 and increased alcohol use following past traumatic events has been demonstrated in the USA with associated adverse health and social consequences. 5 A meta-analysis of 31 population-based studies of mass terrorist attacks concluded that 7.3% of a population can be expected to report increased alcohol consumption in the first two years after the attack, with 20% probability that the prevalence will be as high as 14%.…”
mentioning
confidence: 99%
See 1 more Smart Citation